Ground-Level Pruning at Right Time Improves Flower Yield of Old Plantation of Rosa damascena Without Compromising the Quality of Essential Oil - Shivani,; Mahajan, Mitali; Thakur, Babit Kumar; Pal, Probir Kumar (Frontiers in Plant Science, 2022)
The essential oil of Rosa damascena is extensively used as a key natural ingredient in the perfume and cosmetic industries. However, the productivity and quality of rose oil are a big concern from the old plantation. It is hypothesized that rejuvenation of old rose-plantation through ground-level pruning at right time could improve the yield of flowers and the quality of essential oil. Consequently, a field trial was led-out with ten treatment conditions encompassing two pruning systems (ground-level pruning and ground-level pruning followed by top pruning at end of December) and five different months of ground-level pruning (June to October) to understand the best pruning practices. In this experiment, flower yield ranged from 18.32 to 62.40 q ha−1, and oil content varied from 0.035- 0.049% under different pruning systems and months of pruning. Ground-level pruned plants, irrespective of the month, registered statistically (P ≤ 0.05) more flower yield (618.62 and 473.29 g bush−1) compared with ground-level pruning followed by top pruned plants in both seasons. Average across the pruning system, ground-level pruning in October registered statistically (P≤ 0.05) greater yield of flower (709.10 and 605.13 g bush−1) compared with the ground-level pruning from June- to August. Despite significant variations in flower yield among the treatments, the percentage share of the major compounds particularly β-citronellol+nerol and geraniol in the essential oil were not affected (P≥ 0.05) by the pruning month and pruning system. Thus, the finding suggests that the production from the old plantation of R. damascena can be improved by ground-pruning during October under mild temperate conditions.